Pengaruh Metode Ekstraksi Terhadap Kadar Total Fenolik dan Kadar Total Flavonoid Daun Talas (Colocasia esculenta L.) - Laksmi Ramayani , Septiana; Hildhania Nugraheni , Devi; Robertin Evan Wicaksono, Antonius (Jurnal Farmasi (Journal of Pharmacy), 2021)
Leaves taro ( colocasia esculenta i. Known ) can be used as an antidiabetic drug, due to the compound and flavonoid phenolic bioactive compound. Pharmacological activity an extract dependent on the active compounds contained, more compound higher the levels the more activity. Method extraction affecting concentration or loss of effect of simplicia therapy as some simplicia is relatively unstable and we. The purpose of this research is to know influence different calculation methods extraction to total levels phenolic compounds and total levels flavonoid compounds taro extract leaves. The extraction of leaves taro uses a solvent ethanol 96 % uses the method maceration, microwave-assisted extraction ( MAE), and soxhletasion . The determination of the total content of phenolic compounds uses the method Folin Ciocalteau by an exchange of a standard for comparison of gallic acid. The determination of the level of the total flavonoid uses the method colorimetry with reagent AlCl3 by an exchange of a standard for comparison of quercetin. A method of the extraction of significant impact on the level of the total flavonoid content of phenolic and total extract leaves taro with the value of p<0,05. The total content of phenolic and total flavonoid highest levels on the method the extraction of soxhletasion which is 10,39 mgGAE/g extract and 12,44 mgKE/g. extract.